How much control causes tunneling? Evidence from China - Wenting Chen; Shanmin Li; Crystal Xiaobei Chen (China Journal of Accounting Research, 2017)
We study the dynamic causal effects of the shareholding ratio of controlling shareholder on tunneling behavior in China. We use control-right-transfers as the event to conduct the study. We obtain 394 control-right-transfer samples in China corporate control market from 2001 to 2008. We use related party transactions amount to capture control shareholders' tunneling activities, and make the following findings. Firstly, tunneling behavior is significantly affected by the shareholding ratio of controlling shareholder. Secondly, the relationship between tunneling and shareholding ratio of controlling shareholder takes an N shape (incline-decline-incline). There are at least two turning points in the relationship. Furthermore, firms with shareholding ratios of controlling shareholder that range from 34.46% to 39.01% (8.99-18.04%) exhibit the most (least) severe tunneling. Firm size is significantly positively related to tunneling activities. In addition, the shareholding ratios of the board and the tunneling activities are significantly negatively correlated. These findings imply the shareholding ratio decision of controlling shareholder in control transfers lead to agency problems manifested in China in a particular form of tunneling.
Keywords: G34; G32; G38; 650; Tunneling; Shareholding ratios; Corporate control transfers; Related party transactions